2016
DOI: 10.1093/ajcp/aqw127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implementing the Paris System for Reporting Urine Cytology in the Performance of Urine Cytology

Abstract: The PSRUC seems to improve the performance of urine cytology by limiting the AUC category to cases that are more strongly associated with HGUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 26 publications
9
103
2
Order By: Relevance
“…Hassan et al included 124 urinary cytology cases that were reclassified according to the TPS and also employed a one year time frame between cytology and surgical pathology biopsy specimens. Similar to the current study, they noted a decrease in the number of atypical diagnoses and interestingly included degenerated cells in their AUC diagnosed cases . As indicated, while most other comparative studies had a higher number of cases than the current study, many did not specifically require that the exact sites of the cytologic and biopsy specimens be concordant as we currently present.…”
Section: Discussionsupporting
confidence: 80%
“…Hassan et al included 124 urinary cytology cases that were reclassified according to the TPS and also employed a one year time frame between cytology and surgical pathology biopsy specimens. Similar to the current study, they noted a decrease in the number of atypical diagnoses and interestingly included degenerated cells in their AUC diagnosed cases . As indicated, while most other comparative studies had a higher number of cases than the current study, many did not specifically require that the exact sites of the cytologic and biopsy specimens be concordant as we currently present.…”
Section: Discussionsupporting
confidence: 80%
“…Compared to patients 67 years, patients aged >67 with informative U-FISH test results were more likely to have available follow-up information at 12 months (122/ 177, 68 Table V for confidence intervals). Compared to using all grades of UC as an end point, using only HGUC as an end point resulted in only minor changes of the U-FISH test characteristics, with slight increases in sensitivity and NPV and decreases in specificity and PPV.…”
Section: Resultsmentioning
confidence: 99%
“…25 However, even in the setting of equivocal cytology, the usefulness of U-FISH testing may depend on the indication for urinary cytology (surveillance, hematuria or others), as some authors believe that, U-FISH testing is not indicated in patients with microscopic hematuria, even in patients with persistent atypical urinary cytology who have other risk factors for urothelial carcinoma (older age, significant tobacco history), because of increased cost and the potential for false-positive results, which may lead to unnecessary invasive procedures. 7 Although there is hope that the recently published Paris System of Reporting Urinary Cytology 64-66 will contribute to the standardization and reduction of the frequency of this diagnosis, as has been already suggested by recent studies, 67,68 there is still a need to identify markers that may useful to further stratify the risk of malignancy in patients with a diagnosis of AUC. 63 This is further complicated by the fact that, during our study period there were no agreed-upon criteria for this diagnosis on urinary tract cytologic specimens and the rates with which AUC diagnoses were made have varied widely among institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Cowan et al in their study showed that 40% of the cases with equivocal diagnosis were upgraded to a higher risk group, whereas 25% of those with cytological report which was positive for HGUC in the past, downgraded to a lower risk group after using TPS criteria . In Hassan et al's study, the rate of AUC cases was diminished by 13% . McIntire et al reported reduced rate of AUC from 29% to 13% of cases (rate 50%) .…”
Section: Discussionmentioning
confidence: 96%
“…In one study by Cowan et al, 40% of the cases with confusing diagnosis were reclassified into a higher risk category, while 25% of the cases with positive HGUC were categorized into a lower risk group using TPS criteria . In another study, the frequency of AUC cases declined, and their rate was associated with a subsequent histological diagnosis of increased HGUC . One of the main goals of urinary cytology investigations is the diagnosis of HGUC, an urothelial carcinoma with a high clinical importance.…”
Section: Introductionmentioning
confidence: 99%